Acute Kidney Injury and Chronic Kidney Disease: A Bidirectional Road - Meltem Gürsu; Sami Uzun; Rümeyza Kazancıoğlu; Savaş Öztürk (Haseki Tıp Bülteni, 2017)
Acute kidney injury (AKI) and chronic kidney disease (CKD) have many common points regarding risk factors, etiology, clinical and laboratory factors. We aimed in this review to discuss the outcome, the risk of CKD, cardiovascular and overall mortality risk after AKI, and the mechanisms underlying the relationship between AKI and CKD.